Controlling factors of summer phytoplankton community in the Changjiang (Yangtze River) Estuary and adjacent East China Sea shelf. (15th June 2015) - Jiang, Zhibing; Chen, Jianfang; Zhou, Feng; Shou, Lu; Chen, Quanzhen; Tao, Bangyi; Yan, Xiaojun; Wang, Kui
Abstract: We analyzed the composition and distribution of phytoplankton in relation to physicochemical factors in the Changjiang (Yangtze River) Estuary and adjacent East China Sea shelf in June and August 2009. Diatoms and dinoflagellates dominated the community, particularly in eutrophic inshore waters controlled by the Changjiang Diluted Water (CDW), coastal current, and upwelling. However, high densities of cyanobacteria and cryptophytes were observed in the oligotrophic offshore waters influenced by the Taiwan Warm Current (TWC) and Kuroshio. In June, the northeastward CDW plume combined with the Yellow Sea Coastal Current induced algal bloom in the northern part of the CE. In August, the enhanced CDW formed two narrow, low-salinity tongues that extended eastward and southward (associated with the upwelling and coastal current), resulting in phytoplankton blooms off the CE and in the Zhejiang coastal waters, respectively. Phytoplankton abundance in August was considerably higher than in June, with increased solar radiation, CDW, and upwelling. The maximum abundance occurred on the surface in inshore turbid waters and on the subsurface (5–30 m) in offshore clear waters with increased stratification. Based on multidimensional scaling and cluster analysis, we found appreciable spatio-temporal variations in algal community composition. Different ecological groups corresponded with hydrographic distributions. Canonical correspondence analysis showed that nutrients, salinity, temperature, and suspended particulate matter were the main variables associated with community distribution. We suggest that the variations in summer phytoplankton community are highly correlated with the significant monthly and spatial variability in physicochemical properties, which are primarily controlled by the CDW and TWC. Highlights: Controlling factors of summer phytoplankton in the CE and ECS shelf were examined. Phytoplankton community showed significant spatio-temporal changes during summer. Phytoplankton bloomed around the front of Changjiang Diluted Water (CDW). Limitation of algal growth shifted from light to nutrient across the river plume. Phytoplankton community was primarily controlled by CDW and Taiwan Warm Current.